PVAX1-A20 alleviates colitis in mice by promoting regulatory T cells. Issue 6 (June 2019) - Hu, Tianyong; Hu, Wenhui; Ma, Li; Zeng, Xianhai; Liu, Jiangqi; Cheng, Baohui; Yang, Pingchang; Qiu, Shuqi; Yang, Gui; Chen, Donghui; Liu, Zhiqiang
Abstract: Aim: To investigate whether the intrarectal administration of the ubiquitin E3 ligase A20 (A20) attenuates intestinal inflammation and influences regulatory T cells in experimental colitis. Methods: A dextran sulfate sodium induced chronic colitis mouse model was established. The symptoms and manifestations of colitis and the severity of colonic mucosal inflammation were evaluated. The protective role of A20 expression in the intestine was analyzed after the administration of a pVAX1-A20 recombinant eukaryotic vector, which was encapsulated into poly(L-lactide-co-glycolide) as a nanoparticle. Results: pVAX1-A20 administration markedly ameliorated colonic tissue damage and reduced intestinal inflammation via the suppression of the mucosal mitogen-activated protein kinase and nuclear factor (NF)-κB signaling cascade. Furthermore, pVAX1-A20 promoted the splenic regulatory T cell population and forkhead box P3 expression in colonic tissue. Conclusion: A20 plays a key role in the regulation of intestinal inflammation and that the overexpression of A20 in the intestine protects mice from dextran sulfate sodium induced chronic colitis.